Optimalisasi Kebijakan Program Trias UKS Melalui Edukasi P3K dalam Meningkatkan Respon Kegawatdaruratan pada Siswa di MTS Al-Khairat Kota Gorontalo - Ayudhita Cahyani Daud; Muthmainnah Muthmainnah; Andi Mursyidah; Mesalina Sukardi Massa (Universitas Negeri Gorontalo, 2026)
Emergency situations can occur anytime and anywhere, including in school environments. Limited knowledge and skills among students in providing first aid may increase the risk of worsening victims' conditions before professional medical assistance is available. One strategy to improve students' emergency preparedness is through the optimization of the School Health Program (Trias UKS), particularly its health education component. This community service activity aimed to optimize the implementation of the Trias UKS Program through First Aid Education (P3K) to enhance emergency response capabilities among students at MTs Al-Khairaat Gorontalo City. The program employed lectures, discussions, demonstrations, and hands-on simulation practices supported by PowerPoint presentations, educational videos, leaflets, and first aid kits. The activity was conducted on May 13, 2026, involving 25 students as participants. The results showed that students were able to understand the basic concepts of first aid, identify simple emergency conditions, and perform first aid procedures for cases of fainting, wounds and bleeding, nosebleeds, and choking. Furthermore, participants demonstrated improved preparedness and self-confidence in providing initial responses to emergency situations. First aid education proved effective in supporting the optimization of the Trias UKS Program, particularly in the health education component, while also enhancing students’ emergency response capacities within the school setting.